High contrast ratio prism design in a mini projector - Pan, Jui-Wen; Wang, Hsiang-Hua (My University, 2013)
In this paper, we present a novel prism with the ability to enhance the contrast ratio and maintain the optical efficiency in a digital light processing projection system. The working theorem for the novel prism is derived as well In this novel prism design, the ghost, ray is directed away from the projection lens by a total internal reflection surface. Since the ghost ray does not even enter the projection lens, the contrast ratio enhancement is more effective than that achieved by an asymmetrical stop. Compared with the conventional method, the full-on/full-off contrast ratio is increased from 921:1 to 46347:1 and the American National Standards Institute contrast ratio is increased from 177:1 to 295:1. The imaging system efficiency can maintain at 79.8% under the contrast ratio enhancement process. Ghost ray analysis for the novel prism explains the contrast enhancement well. (C) 2013 Optical Society of America